DIFFERENCES IN THE LEVEL OF ONLINE GAME ADDICTION IN SCIENCE AND IPS HIGH SCHOOL STUDENTS IN THE SOUTH COASTAL AREA OF MUKOMUKO - Imma Rachayu; Diah Selviani (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The World Health Organization will determine addiction to playing games as a mental disorder. The purpose of this study was to fine the results of differences in the level of online game addiction among high school student majoring in science and social sciences. The research method was used quantitative-comparative methods with the t test. The results showed that there were differences in the level of addiction among student majoring in science and social sciences with indicators, namely; salience and tolerance can be seen at the sig (2-tailed) valued of 0,005 < 0,05 and 0,007 < 0,05, then based on the results of the second t test showed that there was no difference in the level of online game addiction among students majoring in science and social sciences, indicators namely; mood modification, relapse, withdrawal, conflict and problem were seen at sig (2-taield) valued of 0,425 > 0,05, 0,744 > 0,05, 0,857 > 0,05, 0,106 > 0,05 and 0,368 > 0,05. This study can be concluded that the difference in the level of online game addiction in students can be intervened gradually and consistently, so that it can influence students’ attitudes and behaviour significantly and is right on target.